(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2020)
The digital economy became the model global economy as the last stage for the devolvement of the economy and it considers as a result of using the information technology in different economic fields, such as what happened in all our life activities. The growth, integration, and sophistication of information technology and communications is changing our society and economy. Consumers now routinely use computer networks to identify sellers, evaluate products and services, compare prices, and extra market leverage. Business use networks even more extensively to conduct and re-engineer production processes , streamline procurement presses , reach new customer and manage internal operation.